POTENSI PENGINDUKSI APOPTOSIS SENYAWA NIKOTINIL DIBUTIL GLUTAMAT ESTER TERHADAP SEL KANKER T47D - Chandra Risdian; Tjandrawati Tjandrawati; Muhamad Hanafi; Yulia Anita; AMJ Putra (Widyariset, 2009)
Nicotinil Dibuthyl Glutamate Ester (NDBGE) is a synthetic compound that is an analog of antibiotic UK3A from mycelium of Streptomyces sp.517-02. This compound was estimated to have anticancer activity similar to UK-3A. The aim of this research was to know the NDBGEs apoptotic inducing potency to human breast cancer T47D in vitro. DMEM + 1% PS + 10% FBS was added to human breast cancer T47D cells until cell concentration reached 1-5x/ 05eells/ml. NDBGE then was diluted by DMSO until 100ppm concentration. Propidium iodide with 50pg/m1 concentration was added to the T47D cells. The analysis was conducted by flow cytometry method. The result was that the apoptosis percentage of the cells was 12,35%.